If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -1m = 2m Solving 24 + -1m = 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 24 + -1m + -2m = 2m + -2m Combine like terms: -1m + -2m = -3m 24 + -3m = 2m + -2m Combine like terms: 2m + -2m = 0 24 + -3m = 0 Add '-24' to each side of the equation. 24 + -24 + -3m = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -3m = 0 + -24 -3m = 0 + -24 Combine like terms: 0 + -24 = -24 -3m = -24 Divide each side by '-3'. m = 8 Simplifying m = 8
| -4.2x+31.5=-65 | | 7n-5=-29+4n | | 10w^2-57w+54=0 | | 210=x+3x-18 | | -3(4p+5)-2(3-14p)=3(8+5p) | | 9+19n-8=8n+86-6n | | 2g+4=1000 | | -5(x+3)+12=13-6x | | 45=28+x | | 10x^3+14x^2-16x= | | 4(0.8g+1.5)=2(3+1.6) | | 3x-36=2x+14 | | s+4=3 | | (5a^3-5a+2)(a-4)= | | x-6.84=4.9 | | 5(x+3)+12=13-6x | | (3x+9)+(3x+8)+(3x)=(3x)+(3x)+(4x+5) | | K-7=-13-2k | | 4t+9=(-8)-13 | | 242=x+5-22 | | 405xy+245x^2= | | 6x+308= | | 5x+6x+2+2=3x+5+7x | | -9x-13+11x-25=2 | | (-10)7= | | f(x)=3e^5x | | 100-2P=40+2P | | 100-2P=40 | | log(x+5)=ln(x-3) | | m^2-5m+14=0 | | 5(2x-8)-7x=x+6 | | 40y^9+5y^4= |